The Crude Oil Price and Speculations: Investigation Using Granger Causality Test - Obadi, Saleh Mothana; Korecek, Matej (International Journal of Energy Economics and Policy, 2018)
This paper examines the up normal move of crude oil prices in the last two decades and tries to relate it with the speculative trading of crude oil in the future markets. The speculators were in the centre of attention during the recent large price moves on the oil market. In this paper we attempted to empirically examine the way, oil speculators operate using the methodology of granger causality. We worked with 4 variables - the price of oil Brent, number of active oil rigs, weekly changes in crude oil stocks and financial positions of investors. Our results show that, on the time period we covered, there exist bidirectional granger causality between oil price and investment positioning of money managers. However we also found the existence of strong Granger causality running directly and indirectly from the fundamental indicators (number of oil rigs and oil stocks) towards money managers financial positions on the oil markets. This finding suggests that even if financial investors have impact on the price of oil, their actions are fundamentally sound. Keywords: Granger Causality, Oil Price, Speculation JEL Classifications: Q41, Q43